Corpus evidence for preference-driven interpretation - Djalali, Alex; Lauer, Sven; Potts, Christopher (Proceedings of the Amsterdam Colloquium, 2011)
We present the Cards corpus of task-oriented dialogues and show how it can inform study of the ways in which discourse is goal and preference-driven. We report on three experimental studies involving underspecified referential expressions and quantifier domain restriction.